The impact of COVID-19 measures on air quality in Turkey - Dursun, Sukru; Sagdic, Mustafa; Toros, Huseyin (TAYLOR & FRANCIS LTD, 2022)
The main objective of this study is to determine the effects of COVID-19 measures on air quality in Turkey. For this investigation, a daily mean of PM10, PM2.5, NO2, CO, O-3,O- and SO2 air pollutant data, provided from the measurement stations run by the Ministry of Environment and Urbanisation and the Istanbul and Izmir Metropolitan Municipalities were used. The R program, an open-code statistics program, was used to generate associated distribution maps using the data obtained. Data for 29 metropolitan cities and the province of Zonguldak, where the pandemic measures were first implemented, were examined for air quality changes. In evaluating whether the COVID-19 measures have had an impact on the air quality of the 30 given cities, two time periods were selected: a period before the COVID-19 measures were implemented (between January 1 and March 15) and the period in which the measures were in force (between March 16 and April 15). In order to take the effects of seasonal conditions on air quality based on the 2020 post-epidemic data into account, the average data from 2018 and 2019 were also compared. This study finds that the restrictions imposed during the COVID-19 pandemic period in the 30 major cities, in which most of the Turkish population lives, significantly improved the air quality. Assuming that some of the measures taken during the pandemic period will become permanent over time (such as the increase in home working, the decrease in air travel thanks to online meetings, the widespread use of distance education, the change in consumption habits and a reduction of waste), the epidemic period is thought to represent a turning point in increasing global air quality.
Keywords: Air quality; Turkey; pandemic; COVID-19 measures; Environmental Sciences & Ecology